1995
DOI: 10.1122/1.550714
|View full text |Cite
|
Sign up to set email alerts
|

Closed‐form solution for the orientation field in a center‐gated disk

Abstract: The orientation field induced by the steady, radially diverging, Newtonian flow between flat, parallel disks is studied. Exact solution for the tbreedimensional rotation of a rigid, hydrodynamically isolated, neutrally buoyant, non-Brownian, slender particle is developed throughout the flow domain from an Eulerian viewpoint. Hence, a closed-form expression is obtained for the orientation distribution, which represents the accurate spatial characterization of the orientation field. In addition, the accuracy of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 46 publications
0
13
0
1
Order By: Relevance
“…The center-gated disc has been studied by other authors (3)(4)(5). Bay and Tucker (3) obtained good agreement for the fiber orientation in the flow direction by tuning the fiber interaction coefficient, and concluded that the closure approximation for & was the main source of error in the predictions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The center-gated disc has been studied by other authors (3)(4)(5). Bay and Tucker (3) obtained good agreement for the fiber orientation in the flow direction by tuning the fiber interaction coefficient, and concluded that the closure approximation for & was the main source of error in the predictions.…”
Section: Introductionmentioning
confidence: 99%
“…In their case the part thickness was b = 3.18 mm and the average fiber length 1 = 0.21 mm. Altan and Rao (5) closed-form solution for the orientation field in a center-gated disc. Based on a study assuming steady, Newtonian flow, and comparing predictions with experimental results from (3), they concluded that both the quadratic and hybrid closure appraximations yielded significant errors in complex suspension flows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Similarly, to align particles across the streamlines, one expands the cross-section of the flow. 5 In a Brownian suspension, as we show, it is possible to align particles with the flow direction without any net contraction of the flow domain normal to the flow direction! Such a capability can improve industrial processes such as fiber spinning.…”
Section: B Closed Flowsmentioning
confidence: 76%
“…28 However, under some other specific flow conditions, the closure approximations give incorrect results. [29][30][31] Albeit the closure approximations generally have relatively higher computational efficiency than the distribution based method, yet the former has lower precision and narrower field of application compared with the latter.…”
Section: Introductionmentioning
confidence: 99%